Pengaruh Ekstrak Alang-alang (Imperata cylindrica L.) Terhadap Pertumbuhan Terong Ungu (Solanum melongena L.) - Laila Farah Diba (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to examine the effect of Imperata cylindrica (alang-alang) extract on the growth of purple eggplant (Solanum melongena L.) across various treatment concentrations, focusing on optimizing plant height, leaf count and width, and weed control. The research employed an experimental design with a randomized block design (RBD), applying alang-alang extract at concentrations of 0% (control), 5%, 10%, and 20%. Observational data included plant height, leaf count, leaf width, and weed count at 7, 14, 21, and 28 days after planting (DAP). The results indicated that a 20% concentration yielded optimal effects, increasing plant height to 8.75 cm, significantly enhancing leaf count and width, and reducing surrounding weeds. These findings support allelopathy theory, demonstrating that phenolic compounds in alang-alang potentially act as natural weed inhibitors and growth stimulators. The study's implications highlight the potential of alang-alang extract as an environmentally friendly alternative for weed control while promoting sustainable eggplant production. Further research is recommended to explore concentrations above 20% to establish the optimal threshold without toxic effects, as well as field testing under varied natural conditions.